Acoustic Michelson-Morley Experiment with an Ultrasonic Range Finder (Global Journal of Science Frontier Research, 2019)
An ultrasonic range finder was mounted on a horizontally rotatable rail at fixed distance, s, to a reflector on the top of a car. The change of the distance reading, s, determined the twoway velocity of sound as a function of the car’s velocity and direction. As a result of this experiment, the out and back velocity c2 was determined to be isotropic – as in the optical case of the Michelson-Morley experiment. Within the experimental error, the velocity was found to vary as c2 (c 2 -v2 )/c.